2012
DOI: 10.1016/j.amjcard.2012.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Vagal Tone as Triggers for Paroxysmal Atrial Fibrillation

Abstract: Alcohol and vagal activity may be important triggers for paroxysmal atrial fibrillation (PAF), but it remains unknown if these associations occur more often than would be expected by chance alone due to the lack of a comparator group in previous studies. We compared the self-reported frequency of these triggers in PAF patients to those with other supraventricular tachycardias (SVT). Consecutive consenting patients presenting for electrophysiology procedures at a single University Medical Center underwent a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…Binge drinking is clearly an important trigger for AF . Short‐term, extensive alcohol consumption can trigger cardiac arrhythmias by altering the electrophysiological properties of the myocardium and influencing both sympathetic and parasympathetic activity . The few prospective studies that have examined the effect of binge drinking found an increased risk of AF among binge drinkers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binge drinking is clearly an important trigger for AF . Short‐term, extensive alcohol consumption can trigger cardiac arrhythmias by altering the electrophysiological properties of the myocardium and influencing both sympathetic and parasympathetic activity . The few prospective studies that have examined the effect of binge drinking found an increased risk of AF among binge drinkers .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cohort studies have generally assessed only the overall quantity of alcohol intake on AF risk. Because binge drinking is a clear trigger for AF, it may increase long‐term risk of AF, even when the overall quantity does not exceed the recommended limits (ie, 1 drink for women and 2 drinks for men per day) . Furthermore, no previous study has estimated the population attributable risk of light‐moderate alcohol intake for AF.…”
Section: Introductionmentioning
confidence: 99%
“…It also suggested that alcohol could trigger AF by vagal activation because patients reporting alcohol as a trigger were more likely to report vagal activation as a trigger 29 . …”
Section: Methodsmentioning
confidence: 99%
“…Studies on familial aggregation demonstrated a comparable risk of 'lone' AF in full and half-siblings (70), which could reflect some interaction between environmental factors (e.g., cigarette smoking, increased alcohol consumption or vigorous sports activity) and a genetic predisposition to AF (34)(35)(36)(37)(38). Indeed, along with the 'traditional' AF risk factors such as aging, cardiovascular and other diseases, etc., other conditions have been also associated with AF in apparently healthy individuals (Table 1) (43,44).…”
Section: Is 'Lone' Af Heritable?mentioning
confidence: 99%
“…At least 2% of general population is currently affected by AF , and the number is expected to rise in the next several decades , presumably because of the increasing number of individuals with ‘novel’ risk factors for AF (e.g., obesity), improved survival of patients with structural heart diseases, aging of the general population and increased awareness of AF among physicians and patients . A number of underlying cardiac and non‐cardiac disorders may predispose to AF (Table ) . Nonetheless, AF sometimes develops in younger individuals without any evident cardiac or other disease.…”
Section: Introductionmentioning
confidence: 99%